Resolvin D1 Suppresses H2O2-Induced Senescence in Fibroblasts by Inducing Autophagy through the miR-1299/ARG2/ARL1 Axis - Hyun Ji Kim; Boram Kim; Hyung Jung Byun; Lu Yu; Tuan Minh Nguyen; Thi Ha Nguyen; Phuong Anh Do; Eun Ji Kim; Kyung Ah Cheong; Kyung Sung Kim; Hiệu Huy Phùng; Mostafizur Rahman; et al. (MDPI AG, 2021)
ARG2 has been reported to inhibit autophagy in vascular endothelial cells and keratinocytes. However, studies of its mechanism of action, its role in skin fibroblasts, and the possibility of promoting autophagy and inhibiting cellular senescence through ARG2 inhibition are lacking. We induced cellular senescence in dermal fibroblasts by using H2O2. H2O2-induced fibroblast senescence was inhibited upon ARG2 knockdown and promoted upon ARG2 overexpression. The microRNA miR-1299 suppressed ARG2 expression, thereby inhibiting fibroblast senescence, and miR-1299 inhibitors promoted dermal fibroblast senescence by upregulating ARG2. Using yeast two-hybrid assay, we found that ARG2 binds to ARL1. ARL1 knockdown inhibited autophagy and ARL1 overexpression promoted it. Resolvin D1 (RvD1) suppressed ARG2 expression and cellular senescence. These data indicate that ARG2 stimulates dermal fibroblast cell senescence by inhibiting autophagy after interacting with ARL1. In addition, RvD1 appears to promote autophagy and inhibit dermal fibroblast senescence by inhibiting ARG2 expression. Taken together, the miR-1299/ARG2/ARL1 axis emerges as a novel mechanism of the ARG2-induced inhibition of autophagy. Furthermore, these results indicate that miR-1299 and pro-resolving lipids, including RvD1, are likely involved in inhibiting cellular senescence by inducing autophagy.